Дослідження впливу способу переробки винограду на фенольний комплекс столових вин - Циганкова, Олена Вікторівна; Білько, Марина Володимирівна (НТУ "ХПІ", 2016)
Представлені результати досліджень фенольного комплексу рожевих і червоних виноматеріалів із винограду сортів Санджовезе, Сіра, Пті Вердо. Встановлено, що спосіб переробки винограду істотно впливає на якісний і кількісний склад фенольного комплексу. Висока масова концентрація біофлавоноїдів була в схемах переробки винограду, що передбачали підброджування і бродіння м’язги. Проведено порівняльний аналіз органолептичних, фізико-хімічних і оптичних показників якості виноматеріалів. Перспективні для України сорти винограду Санджовезе, Сіра, Пті Вердо мають хороший потенціал для отримання вин з високою біологічною цінністю.

The aim of the work is to find the effect of grapes processing method on the phenolic complex of the wine stock. The test material was pink and red dry table wine stock, prepared according to various schemes of grape varieties Petit Verdot, Sangiovese, Syrah, Cabernet Sauvignon (check). The determination of phenolic compounds was performed according to the method with the chromatograph Agilent Technologies, Model 1100. The results of the chromatographic analysis made it possible to determine a significant difference between qualitative composition and quantitative content of anthocyanins, other bioflavonols and non-condensed tannins in wine stock produced from grapes of different varieties. The highest content of phenolic compounds was in wine stocks from the grapes Petit Verdot, the smallest was in Syrah.
Investigation of the effect of grapes processing method on the phenolic complex of table wines
Keywords: виноматеріали; флавоноїди; антоціани; катехіни; wine stocks; flavonols; anthocyantins